Challenges of common agricultural policy development - Nelė Jurkėnaitė; Artiom Volkov (Business: Theory and Practice, 2011)
Common Agricultural Policy has strengthened the economy of the EU since the 6th decade of the 20th  century. Agriculture is the sensitive sector of economic activity,and consequently CAP constantly evolves influenced by alternating problems of the sector. This evolution is accompanied by reforms, which increase efficiency of the CAP tools. The current CAP is criticized because its objectives do not meet challenges of the agricultural and rural development. CAP for 2014–2020 is being realized as a new phase of policy evolution and its outcome depends on the selection of the appropriate development directions and the determination of workable tools. Identification of CAP development directions is empowered by the provided in the paper research, which establish the most important CAP problems and challenges.